Obiski na domu pri ljudeh po amputaciji spodnjega uda - Križnar, Agata (Rehabilitacija (Ljubljana), 2020)
Background: A person with lower limb loss (LLL) often reaches the goals set during rehabilitation, but afterwards at home he or she may become dependent again due to the barriers. These limitations can be eliminated by professional consulting at home. The main aim of our study was to assess the home environment, namely safety and independence at performing basic daily living activities, individual meaningful activities and limitations that individuals have while performing activities at home. Methods: An occupational therapist and an electrical engineer assessed barriers and facilitators that elderly people with LLL have at their homes using the Canadian Occupational Performance Measure and a semistuctured interview. They have advised them to use various assistive devices and modifications of the environment. Results: The visited elderly people with LLL have barriers in two to five places. Most of them have barriers at access to the entrance and wider environment, toilets and bathroom. We have advised them to use four to eight different assistive devices, modifications, services and/or to avoid some activities. The most frequent suggested device was a reacher/grabber to reach objects from the heights and from the ground. Conclusions: Despite the consulting during rehabilitation, the participants with lower limb loss still have many barriers at home, which influence their safety and independence in meaningful activities.
Keywords: amputacija; Amputation; assistive devices; delovna terapija; home visit; Lower Extremity; lower limb loss; modifications of environment; obisk na domu; Occupational Therapy; prilagoditev okolja; pripomočki; rehabilitation; spodnji ud